Analisis Pengaruh Nilai Beban Unit Terhadap Efisiensi dan Heat Rate Turbin Pada Pltu Moramo - Ilham, Muhammad; Salimin, Salimin; Aksar, Prinob (Teknik Mesin Universitas Halu Oleo, 2021)
Moramo steam power plant is one of steam power plant in Indonesia that using coal as it fuels with capacity of 2x50 MW. Power produced by Moramo steam power plant is not always in constant condition because of fluctuation power in distribution grid with corresponding of power demand. One of the main indicators of steam turbine performance is the efficiency of steam turbine cycle and turbine heat rate. This research conducted to analyzes the effect of changes in power produced by Moramo steam power plant on the efficiency and turbine heat rate using a thermodynamic analysis approach and energy input-output methods. Analyzed data in this research is actual data during normal operation that taken from Distributed Control System (DCS). Results of this research indicated that the more the power produced by Moramo steam power plant the better of performance of its steam turbine. It is showed by the increase of average efficiency from 39.138% on 30 MW Net load to 39.369 % on 40 MW Net load, and increase to 39.976 % on 50 MW Net load. Furthermore, the increase of performance also showed by the decrease of its average turbine heat rate from 10137.79 kJ/kWh on 30 MW Net load to 9633.95 kJ/kWh on 40 MW Net load, and decrease to 9333.77 kJ/kWh on 50 MW Net load.Keywords: Load, efficiency, heat rate, steam power plant, steam turbine